CSR as an element of based-value marketing. Implementation of corporate social responsibility by the DANONE GROUP in Poland - Howaniec, H. B. (Видавництво Львівської політехніки, 2013)
The system changes, including in Poland, have forced a change in approach to the market. Implementation of the marketing concept without providing real value for the customer, taking into account other interest groups or using traditional media is becoming – at least for certain groups of consumers – obsolete. This article presents the definition of the marketing concept, narrowing to its determination from the perspective of the tools and its goals, presents the concept of value-based marketing and its specificity by presenting as an example – delivering value through the implementation of the concept of corporate social responsibility. Системні зміни, які відбуваються зокрема й у Польщі, змусили змінити підхід до маркетингу. Впровадження маркетингової концепції без надання реальної вартості для споживача, беручи до уваги інтереси інших груп чи використовуючи традиційні засоби маркетингових комунікацій, для певних груп стає недоцільним. Визначено маркетингову концепцію, деталізуючи її з точки зору інструментарію та цілей, представлено концепцію орієнтованого на вартість маркетингу і його специфіку з використанням прикладу – надання вартості впровадженням концепції корпоративної соціальної відповідальності.
CSR як елемент орієнтованого на вартість маркетингу. Впровадження корпоративної соціальної відповідальності у DANONE GROUP у Польщі
Keywords: CSR; based-value marketing; орієнтований на вартість CSR; CSR; маркетинг